2021
DOI: 10.1051/0004-6361/202038590
|View full text |Cite
|
Sign up to set email alerts
|

Accretion-to-jet energy conversion efficiency in GW170817

Abstract: Gamma-ray bursts (GRBs) are thought to be produced by short-lived, supercritical accretion onto a newborn compact object. Some process is believed to tap energy from the compact object, or the accretion disc, powering the launch of a relativistic jet. For the first time, we can construct independent estimates of the GRB jet energy and of the mass in the accretion disc in its central engine; this is thanks to gravitational wave observations of the GW170817 binary neutron star merger by the Laser Interferometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 180 publications
(195 reference statements)
2
13
0
Order By: Relevance
“…The electromagnetic counterpart of GW170817 strongly disfavoured a long-lived NS remnant, which would otherwise overproduce the X-ray flux at late time and inject too much energy in the relativistic ejecta to be consistent with the afterglow data (e.g. Granot, Guetta & Gill 2017;Margutti et al 2018;Pooley et al 2018;Xie, Zrake & MacFadyen 2018;Margalit & Metzger 2019;Makhathini et al 2020;Salafia & Giacomazzo 2020). Based on the assumption that GW170817 made a BH, many authors have concluded that the maximum mass of a non-rotating NS is M TOV 2.3 M (Margalit & Metzger 2017;Rezzolla, Most & Weih 2018;Shibata et al 2019; but see Ai, Gao & Zhang 2020, for a discussion of the less likely case that GW170817 did not make a BH).…”
mentioning
confidence: 96%
“…The electromagnetic counterpart of GW170817 strongly disfavoured a long-lived NS remnant, which would otherwise overproduce the X-ray flux at late time and inject too much energy in the relativistic ejecta to be consistent with the afterglow data (e.g. Granot, Guetta & Gill 2017;Margutti et al 2018;Pooley et al 2018;Xie, Zrake & MacFadyen 2018;Margalit & Metzger 2019;Makhathini et al 2020;Salafia & Giacomazzo 2020). Based on the assumption that GW170817 made a BH, many authors have concluded that the maximum mass of a non-rotating NS is M TOV 2.3 M (Margalit & Metzger 2017;Rezzolla, Most & Weih 2018;Shibata et al 2019; but see Ai, Gao & Zhang 2020, for a discussion of the less likely case that GW170817 did not make a BH).…”
mentioning
confidence: 96%
“…It also showed the importance of population studies required to disentangle the microphysics of the source and its interaction with the environment, from the source geometry and energetics. Increasing the number of joint detections will make it possible to determine the equation of state of neutron stars 171 , to probe the properties of different components of the mass ejected during and after the merger [172][173][174] , to understand if the BNS mergers are the primary channel of formation of heavy elements and the details of the nuclear physics relevant to nucleosynthesis 175 , and to understand the structure of the relativistic jets and the physics behind their formation 176,177 .…”
Section: Dawn Of a New Multi-messenger Eramentioning
confidence: 99%
“…Two often proposed candidates are the Blandford-Znajek (BZ) mechanism (Blandford & Znajek 1977) and neutrino pair annihilation (Eichler et al 1989;Mészáros & Rees 1992;Just et al 2016). Salafia & Giacomazzo (2021) (hereafter referred to as SG21) discuss both mechanisms in detail and derive disk accretion-to-jet energy conversion efficiencies. For GW170817, they calculate that both mechanisms have efficiencies which are consistent with GRB170817 and they can therefore not distinguish between the two.…”
Section: Grb Jetmentioning
confidence: 99%